PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP DISIPLIN KERJA DAN KINERJA PEGAWAI KANTOR KABUPATEN BARITO UTARA KALIMANTAN TENGAH: - TAJERI (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2017)
This study included a survey with this type of research design and explanatory research using quantitative approaches. Data were collected using a questionnaire to 135 respondents who are employees of North Barito regence, Central Kalimantan. Samples were taken using a technique/method slovin. To examine patterns of relationships are built, researchers use analytical tool Structural Equation Modelling (SEM) with the help of the program Analysis of Moment Structures (AMOS) version 6.0. The results of this study indicate that : 1) leadership variables affect the variables of work discipline employees, 2) leadership variables have no effect on employee performance variables, 3) organizational cultural variables influence the variables of work discipline employees; 4) organizational cultural variables influence employee performance variables; 5) working environment variables affect the variables if work discipline employees, 6) work environment variables had no effect on employee performance variables; 7) motivational affect the variables of work discipline employees; 8) motivational variables influence employee performance variables, and 9) the variable labor discipline variables affect the performance of employees. Leadership does not significantly affect the performance of employees, although labor discipline affect the performance of employees, it provides practical implications for leaders. This means that if a leader wants high- performance employees, then the surt of increase in employee discipline. Organizational culture significantly influence labor discipline or the performance of employees it provides practical implications for leaders. This means that if a leader wants high performans, then the leader can start from creating a strong culture. The total contribution of the variables of leadership, organizational culture, work environment, and motivation toward variable of work discipline (Y1) of 32,62%. This means there is still 67,38% of other variables that can not be explained by the variables involved in shaping the work-discipline variable (Y1). The total contribution of the variables of leadership, organizational culture, work environment, motivation, and discipline employees working in the performance variable (Y2) of 27,82%. This means there is still 72,81% of other variables that can not be explained by the variables involved in forming employee performance variable (Y2).